2003
DOI: 10.1128/aac.47.12.3789-3794.2003
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations in Plasma, Urinary Excretion, andBactericidal Activity of Linezolid (600 Milligrams) versusThose of Ciprofloxacin (500 Milligrams) inHealthy Volunteers Receiving a Single OralDose

Abstract: In a randomized crossover study, 12 volunteers (6 males, 6 females) received a single oral dose of 600 mg of linezolid or 500 mg of ciprofloxacin to assess the concentrations in plasma (up to 24 h), urinary excretion (by high-pressure liquid chromatography), and bactericidal titers in urine (UBT) at intervals up to 120 h. The mean maximum concentration of linezolid in plasma was 13.1 mg/liter, and that of ciprofloxacin was 2.46 mg/liter. The median cumulative levels of renal excretion of the administered dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…TOPO II-targeting drugs are apoptosis-inducing drugs, and both isoforms of TOPO II, alpha and beta, are inhibited by the chemotherapeutic agent etoposide (22). We found that etoposide had no effect on COX expression, adhesion molecule expression, and cytokine production in the absence and presence of IL-18 (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…TOPO II-targeting drugs are apoptosis-inducing drugs, and both isoforms of TOPO II, alpha and beta, are inhibited by the chemotherapeutic agent etoposide (22). We found that etoposide had no effect on COX expression, adhesion molecule expression, and cytokine production in the absence and presence of IL-18 (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…The drug concentrations in serum and urine samples were measured by comparison with a serum and urine calibration row, respectively (24). MICs, minimal bactericidal concentrations (MBCs), and urinary bactericidal titers were determined as published previously (17,26).The bacterial strains used in this study and ciprofloxacin and levofloxacin MICs are depicted in Table 1. The MBCs of levofloxacin and ciprofloxacin were similar to the corresponding MICs for all strains tested.…”
mentioning
confidence: 99%
“…The drug concentrations in serum and urine samples were measured by comparison with a serum and urine calibration row, respectively (24). MICs, minimal bactericidal concentrations (MBCs), and urinary bactericidal titers were determined as published previously (17,26).…”
mentioning
confidence: 99%
“…Oxazolidinones active against Gram-positive bacteria may be considered for use in the treatment of cUTIs because of the presence of Gram-positive uropathogens (45,46). In a mouse pyelonephritis infection model, RBx 11760 and linezolid showed comparable efficacy, resulting in stasis when administered at 20 mg/kg four times a day.…”
Section: Discussionmentioning
confidence: 99%